High fat diet (HFD) induced hepatic lipogenic metabolism and lipotoxicity via Parkin-dependent mitophagy and Errα signal of Pelteobagrus fulvidraco - Angen Yu; Zhiwei Hao; Xiaolei Wei; Xiaoying Tan; Ester Zito; Hua Zheng; Zhi Luo (Journal of Animal Science and Biotechnology)
Abstract Background Mitophagy is an essential cellular autophagic process which maintains mitochondrial homeostasis, but its role in high fat diet (HFD)-induced lipid accumulation is unclear in the yellow catfish. Thus, this study aimed to elucidate mechanism of mitochondria mediating HFD-induced hepatic fat accumulation. Results In the present study, yellow catfish were fed three diets with dietary fat at 6.31% (low fat; LFD, control), 12.03% (middle fat; MFD) and 15.32% (high fat; HFD), respectively, for 8 weeks. High dietary fat addition raised hepatic lipid accumulation, and declined mRNA and protein levels of Parkin-dependent mitophagy, down-regulated the Parkin protein expression and the estrogen-related receptor alpha (Errα) ubiquitination, and induced Errα protein levels; fatty acid (FA) incubation reduced Parkin-dependent mitophagy, inhibited Errα ubiquitination and increased Errα protein expression, and raised TG accumulation. Furthermore, yellow catfish hepatocytes were isolated and cultured. Nicotinamide mononucleotide, N-acetyl-L-cysteine, Parkin and errα siRNA knockdown were used under FA incubation, respectively. Parkin downregulation mediated FA incubation-induced TG accumulation and mitoautophagic inhibition; Parkin ubiquitinated Errα, and K63 was an important ubiquitination site for deubiquitinating Parkin activity; Errα targets fas, acca and pparγ genes, whose activation contributed to FA-induced lipogenesis and lipid accumulation. Thus, high fat diet (HFD) and FA incubation inhibited Parkin activity, suppressed mitophagy and activated Errα pathway, and induced hepatic lipogenic metabolism and lipotoxicity. Conclusions Overall, our study provided new targets against HFD-induced hepatic lipid accumulation and non-alcoholic fatty liver disease in the vertebrates.